Improving Collaboration Skills and Student Learning Outcomes in Cross-Interest Subjects (Biology) through the Problem Based Learning Model - mahda mumtahanah; Ima agung nurcahyo; cicilia novi primiani (Magister Pendidikan Biologi, Universitas Negeri Medan, 2023)
This study aims to improve collaboration skills and learning outcomes of students majoring in Social Sciences (IIS) in Biology cross-interest subjects through the Problem-Based Learning learning model. This type of research is classroom action research (CAR), which consists of 2 cycles, where each cycle consists of planning, action, observation, and reflection stages. The research subjects were 32 class XI IIS 3 students at SMAN 6 Madiun. The instruments used in this study were observation sheets and test sheets. The results obtained were an increase in collaboration with an average score of 74% in cycle 1 and 83% in cycle 2 with a good value category. From these results, it is known that the percentage increase from cycle 1 to cycle 2 is 9%. The results obtained showed an increase in learning outcomes, with the average pretest score in cycle 1 being 48 increasing to 62 in cycle 2 so the percentage increase from cycle 1 to cycle 2 was 29%. While the average post-test score in cycle 1 was 75, it increased to 81 in cycle 2 so that the increase in posttest learning outcomes from cycle 1 to cycle 2 was 8%. The conclusion from this study is that the Problem-Based Learning learning model can improve collaboration skills and learning outcomes of class XI IIS 3 students of SMAN 6 Madiun in cross-biology subjects.